Livestock in the livelihoods of the underprivileged communities in India: A review - Rangnekar, D.V. (International Livestock Research Institute, 2006)
In India underprivileged families account for about one-fourth of the population and contribute a major part of livestock production. Livestock are central to their livelihoods and culture. An extensive review of formal and grey literature addressed the premise that a good understanding by the research and development community of the role of livestock in the livelihoods of the underprivileged and their production and marketing systems are needed to guide effective research and development (R&D) aiming to alleviate poverty. The review covered cattle, buffalo, goat, sheep, pig and poultry and their output, input, risk, asset and social functions when kept by India’s underprivileged families. It examined the factors affecting where and how the livestock were managed. It is concluded that to improve the livelihoods of the underprivileged families through livestock, inter-disciplinary action-oriented research should target communities in contrasting agro-ecozones in central, eastern and north-eastern India with priority given to small-stock, specifically goats, pigs and backyard poultry. The review notes that there is paucity of information and of projects on underprivileged communities and small-stock, particularly in the suggested target regions. It is recommended that the research should start by ensuring a shared understanding between research-for-development teams and the underprivileged communities of the preferences of the communities for specific types of livestock, their perceptions (particularly of the women) about the roles and functions of the livestock in livelihood strategies, and what, from their perspective, constitutes improvement. Subsequently, action-oriented participatory research would identify and address constraints to, and opportunities for, improving livestock-based productivity and profitability and the non-market functions of livestock. The recommended approach will require a change in paradigm from the conventional reductionist, animal-level research to peoplecentred, participatory and holistic methods in iterative research-for-development programmes that are inter-disciplinary, multi-institutional and, ideally, multi-locational to facilitate cross-site lesson learning. Given the increasing demand for livestock products, this is an opportune time for animal scientists to make an impact on the livelihoods of the underprivileged by adopting this change in the research paradigm.